Clinical outcomes for nasopharyngeal cancer with intracranial extension after taxane-based induction chemotherapy and concurrent chemo-radiotherapy in the modern era - Sarbani Ghosh-Laskar (KeAi Communications Co., Ltd., 2020)
Objective: To evaluate the survival outcomes for a cohort of nasopharyngeal cancer with intracranial extension (ICE) treated with induction chemotherapy (ICT) followed by chemo-intensity-modulated radiotherapy (CTRT) at a tertiary cancer center. Methods: We retrospectively analyzed 45 patients with histologically proven, non-metastatic NPC with ICE treated at our institute between October 2008 and October 2016. Patients were classified as minor ICE or major ICE, based on the extent of ICE. All the patients received 2–3 cycles of a taxane-based ICT regimen followed by CTRT. Radiotherapy was delivered with “risk-adapted” intensity-modulated radiotherapy (IMRT) technique in all patients. Results: After a median follow up of 45 months (range: 8–113 months), the estimated 5-year DFS, LRFS, DMFS, and OS of the entire cohort was 58%, 82%, 67% and 74% respectively. On multivariate analysis, histological subtype was an independent predictor of LRFS, and age was an independent predictor of DFS. The extent of ICE showed only a trend towards worse DFS (P = 0.06). None of the factors significantly predicted for DMFS or OS. Gender, N-stage, and response to ICT did not significantly affect any of the outcomes. Grade 2 or worse subcutaneous fibrosis was seen in 22% of patients and grade 2 or worse xerostomia was seen in 24% of patients at last follow up. Thirty-three percent of the patients developed clinical hypothyroidism at last follow up. None of the patients experienced any neurological or vascular complications. Conclusions: Taxane-based induction chemotherapy followed by chemo-intensity modulated radiotherapy resulted in excellent locoregional control and survival with acceptable toxicities in patients of nasopharyngeal cancer with intracranial extension. Distant metastasis continues to be the predominant problem in these patients.